2015
DOI: 10.1186/s12939-014-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Refusal to enrol in Ghana’s National Health Insurance Scheme: is affordability the problem?

Abstract: Background: Access to health insurance is expected to have positive effect in improving access to healthcare and offer financial risk protection to households. Ghana began the implementation of a National Health Insurance Scheme (NHIS) in 2004 as a way to ensure equitable access to basic healthcare for all residents. After a decade of its implementation, national coverage is just about 34% of the national population. Affordability of the NHIS contribution is often cited by households as a major barrier to enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 28 publications
11
97
1
Order By: Relevance
“…The findings of this study have implications for reducing inequity in access to healthcare, especially in light of the ongoing challenges to improve NHIS coverage [23,45] and efforts to achieve Universal Health Coverage. The results suggest that enabling factors (wealth) were a strong predictor for the use of both public and private health facilities.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study have implications for reducing inequity in access to healthcare, especially in light of the ongoing challenges to improve NHIS coverage [23,45] and efforts to achieve Universal Health Coverage. The results suggest that enabling factors (wealth) were a strong predictor for the use of both public and private health facilities.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…However, it has also been reported that the NHIS contribution from the formal employment sector is very regressive, in that people with lower income contribute a higher share of their income than do people with higher income [21]. Coverage also remains low, with only 34% of people being active members (valid cardholder members) of the NHIS [23]. Furthermore, it is mainly public and mission-based healthcare facilities which provide healthcare through the NHIS; most private for-profit facilities require payment at the point of use.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have attributed the low coverage of the scheme to unaffordable premium, perceived poor quality of health services, lack of trust, and confusion over basic details of the scheme, among others [8][9][10]. It has been found that certain groups of persons, especially the poor are systematically excluded from the NHIS [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Insurance premiums and registration fees remain as obstacles to enrolment for the poor, many are simply left unattended without any form of protection [27]. For people in the poorest quintile, premium imposes a heavy burden as it takes up 11.4% of their non-food expenditure while it only takes up 5.9% for general households [28]. A recent study done in Ghana revealed that as share of OOP payment for healthcare in total household expenditure increases, impoverishment deepens [37].…”
Section: Discussionmentioning
confidence: 99%